Hallux rigidus: Arthroplasty or arthrodesis. What technique produces better results? - Grande del Arco, Jessica (Revista Internacional de Ciencias Podológicas, 2016)
Hallux rígidus (HR) affects the first metatarsophalangeal joint (MTPJ) between 35% and 60% of the population over 65 years and there are multiple ways of treatment. Depending on the radiological stage where you find the deformity determines the procedure to be performed; in the early stages cheilectomy techniques and corrective osteotomy is performed while the more advanced ratings, the surgeon chooses destructive techniques considered as arthrodesis and arthroplasty. This final of degree project aims to focus on 1 MTPJ destructive techniques to clarify which of the procedures generates better results by a number of parameters; outcomes of the American Orthopaedic Foot scale and Ankle Society Hallux metatarsophalangeal Interphalangeal-scale (AOFAS), range of motion (ROM) of the 1ºAMTF, radiological classification. As for the implant arthroplasty technique, this article offers information on material and design that generates better relating to patient characteristics such as age, inflammatory joint diseases, viability and durability of the implant results. The conclusion from this review is that the values obtained in the arthrodesis according AOFAS decrease due to loss of mobility, but both techniques have similar values of effectiveness and concludes with the decision that the technique used is determined taking into account various factors and patient characteristics. Keywords: Hallux rígidus; (Hallux Rígidus) and surgery treatment; Hallux Rígidus arthrodesis; Hallux Rígidus arthroplasty; Hallux Rígidus (arthroplasty and arthrodesis).